Comparative study of the clinical effect produced by the first Class® and the pendulum in patients trated at the College of Dentistry, University of Antioquia: a radiographic and model analysis - Betancur-P., John Jairo; Carvajal-F., Álvaro; Jaramillo-V., Pedro María; García-B., Jenny; Madrigal-M., Nora; Lopera-A., Margarita (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The purpose of this research was to establish and compare the clinical and radiographic results obtained during the four month use of the pendulum and the First class® in relation with its craneofacial, dental, and soft tissue effects in patients who had indicated as part of their treatment plan, a distalization of their first upper molars. The sample consisted of 27 subjects between 12 and 17 years of age: 11 treated with pendulum, 8 treated with First class®, and 8 controls to discard any changes due to growth. All patients received inicial Panoramic X-rays, inicial and final lateral cephalograms; 1:1 standardized pictures of study casts at the beginning, second and fourth months of treatment. The radiographic results showed there were no significant changes in the skeletal structures. At the dento-alveolar level an average molar distalization of 4.68 ± 4.9 mm was observed with the pendulum and of 2.05 ± 4.06 mm with the First class® both of which were accompanied by distal inclination (12.2º pendulum, 3.2º First class®) and intrusion (0.55 and 0.037 mm respectively) with an assymetric right – left behavior. For each millimeter of molar distalization there was an increment in incisal labialization of 0.9º with the pendulum and 3.0º with the First class® accompanied by a decrease in the nasolabial angle (-5.45º with the pendulum and -6.0º with First class®) and an upper lip protrusion (1.59 and 1.07 mm respectively). The dental casts showed a rotational change in the molar with a heterogenous behavior; with both pendulum and First class®, rotations in opposite directions were observed: distopalatal (+) y distolabial (-). The total average was positive in both, being greater for the First class® (5.87°) than for the pendulum (4.3°), conserving a right-left asymmetric pattern. The effectiveness of the anchorage offered by the palatal acrylic button should be questioned, since there was evidence of anterior displacement of this structure with a negative labialization effect on the anchorage teeth.